Benefit finding trajectories in cancer patients receiving psychological care: Predictors and relations to depressive and anxiety symptoms. Issue 2 (15th November 2017) - Zhu, Lei; Ranchor, Adelita V.; Helgeson, Vicki S.; van der Lee, Marije; Garssen, Bert; Stewart, Roy E.; Sanderman, Robbert; Schroevers, Maya J.
Abstract : Objectives: This study aimed to (1) identify benefit finding trajectories in cancer patients receiving psychological care; (2) examine associations of benefit finding trajectories with levels of and changes in psychological symptoms; and (3) examine whether socio‐demographic and medical characteristics distinguished trajectories. Design: Naturalistic longitudinal study design. Methods: Participants were 241 cancer patients receiving psychological care at specialized psycho‐oncological institutions in the Netherlands. Data were collected before starting psychological care, and three and 9 months thereafter. Latent class growth analysis was performed to identify benefit finding trajectories. Results: Five benefit finding trajectories were identified: 'high level‐stable' (8%), 'very low level‐small increase' (16%), 'low level‐small increase' (39%), 'low level‐large increase' (9%), and 'moderate level‐stable' (28%). People in distinct benefit finding trajectories reported significant differential courses of depression but not of anxiety symptoms. Compared with the other four trajectories, people in the 'low level‐large increase' trajectory reported the largest decreases in depression over time. Perceptions of cancer prognosis distinguished these trajectories, such that people with a favourable prognosis were more likely to belong to the 'high level‐stable' trajectory, while people perceiving an uncertain prognosis were more likely to belong to the 'low level‐large increase' trajectory of benefit finding. Conclusions: Cancer patients showed distinct benefit finding trajectories during psychological care. A small proportion reporting a large increase in benefit finding were also most likely to show decreases in depressive symptoms over time. These findings suggest a relation between perceiving benefits from cancer experience and improved psychological functioning in cancer patients receiving psychological care. Statement of contribution What is already known on this subject? People vary in course of benefit finding (BF) after trauma, with some experiencing enhanced BF and others decreased BF. Empirical studies have identified subgroups of cancer patients with distinct BF trajectories. What does this study add? This is the first study showing that cancer patients followed different BF trajectories during psychological care. Only a small proportion experienced clinically meaningful increases in BF over time. More attention is needed for cancer patients with decreased BF, as they are at a higher risk of remaining depressed.